Need Analysis of Listening Skills in the EFL Class at Sulawesi Barat University - Putu Wahyu Sudewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Listening is clearly the weakest skill of EFL students who encounter different kinds of listening problems. This research analyzed student needs analysis of listening skills in EFL learners at Sulawesi Barat University. This study was conducted to identify students' listening obstacle and identify their needs analysis. The questionnaire was conducted to answer the following questions. (1) What are the barriers to the development of students' listening skills? And (2) what are the needs of students regarding listening? 124 EFL students from six different classes were voluntarily selected for the study. The data was gathered by questionnaire. The results of the study showed several reasons that hinder a student's hearing were speaking fast, speaking quietly, different accents and pronunciation, and a group of people talking at the same time. Students' needs for listening comprehension are as follows: students need to recognize English lecturers, students need to learn how to take effective notes and ask for repetition or explanations, students need to recognize long explanations and instructions in English, different accents and pronunciations need to be recognized and students need to increase their vocabulary.